2018
DOI: 10.1016/j.neuroimage.2018.06.070
|View full text |Cite
|
Sign up to set email alerts
|

Sounds enhance visual completion processes

Abstract: Everyday vision includes the detection of stimuli, figure-ground segregation, as well as object localization and recognition. Such processes must often surmount impoverished or noisy conditions; borders are perceived despite occlusion or absent contrast gradients. These illusory contours (ICs) are an example of so-called mid-level vision, with an event-related potential (ERP) correlate at ∼100-150 ms post-stimulus onset and originating within lateral-occipital cortices (the IC). Presently, visual completion pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 76 publications
1
18
0
Order By: Relevance
“…It has been shown that sounds: i) improve the detection and discrimination of concurrently presented visual stimuli (e.g. McDonald et al, 2000; Gleiss and Kayser, 2014; Kayser and Kayser, 2018), ii) increase their subjective intensity (Stormer et al, 2009; Odgaard et al, 2004; Lovelace et al, 2003), iii) speed up responses to visual targets and enhance their attentional selection (Brang et al, 2015; Cappe et al, 2010; Matusz & Eimer, 2011, 2013; Matusz et al 2015a; 2019a, 2019b; also Kayser et al, 2017), and iv) even contribute to visual perceptual filling-in (Tivadar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that sounds: i) improve the detection and discrimination of concurrently presented visual stimuli (e.g. McDonald et al, 2000; Gleiss and Kayser, 2014; Kayser and Kayser, 2018), ii) increase their subjective intensity (Stormer et al, 2009; Odgaard et al, 2004; Lovelace et al, 2003), iii) speed up responses to visual targets and enhance their attentional selection (Brang et al, 2015; Cappe et al, 2010; Matusz & Eimer, 2011, 2013; Matusz et al 2015a; 2019a, 2019b; also Kayser et al, 2017), and iv) even contribute to visual perceptual filling-in (Tivadar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The present results lend further support to the notion that sounds can enhance the excitability of visual cortices. In our prior work (Tivadar et al, 2018), we observed that an event-related potential signature of illusory contour sensitivity was enhanced by the presence of task-irrelevant sounds. A network of brain regions involved in this effect included not only LOC and the intra-parietal lobule, as previously observed in ERP studies of IC sensitivity (Murray & Herrmann, 2013), but also V1.…”
Section: Discussionmentioning
confidence: 72%
“…Instead, there was a general reduction in hit rates under multisensory versus unisensory conditions. Tivadar et al (2018) observed electrophysiological enhancement of event-related potential indices of illusory contour sensitivity despite near-ceiling performance and thus the absence of any concomitant behavioural effects when the task involved discrimination of IC presence versus absence.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations